KONSEP PEMIKIRAN SEKULARISASI NURCHOLISH MADJID SEBUAH FENOMENOLOGI AGAMA - Nulhakim, Lukman (Risâlah, Jurnal Pendidikan dan Studi Islam, 2020)
This research tries to explore the thought of Nurkholish Madjid as a dynamic phenomenology of religion in secularization discourse, this article wants to discuss the discourse offered by Nurcholish Madjid about Secularization, looking at the cultural localities of Indonesia and socio-politics, then of course there are many ways of looking at Muslim ideas in responding to the discourse of renewal. in Islamic thought Nurkholish Madjid. Keywords: Secularism and Phenomenology of Religion.